2008
DOI: 10.1002/prot.22074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipid composition on buforin II structure and membrane entry

Abstract: Buforin II is a 21-amino acid polycationic antimicrobial peptide derived from a peptide originally isolated from the stomach tissue of the Asian toad Bufo bufo gargarizans. It is hypothesized to target a wide range of bacteria by translocating into cells without membrane permeabilization and binding to nucleic acids. Previous research found that the structure and membrane interactions of buforin II are related to lipid composition. In this study, we used molecular dynamics (MD) simulations along with lipid ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 62 publications
6
28
1
1
Order By: Relevance
“…As previously reported, BF2 is able to enter into the cytoplasmic membrane without generating significant depolarization and/or cellular leakage (Table 3). This pattern is consistent with the currently accepted mechanism of BF2 action that establishes its ability to translocate into bacteria without disrupting the membrane [9,10,11,12,13,14]. Our findings unveil for the first time the capacity of BF2 to agglutinate E. coli cells and liposomes when increasing the peptide concentration above its effective antimicrobial concentration.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As previously reported, BF2 is able to enter into the cytoplasmic membrane without generating significant depolarization and/or cellular leakage (Table 3). This pattern is consistent with the currently accepted mechanism of BF2 action that establishes its ability to translocate into bacteria without disrupting the membrane [9,10,11,12,13,14]. Our findings unveil for the first time the capacity of BF2 to agglutinate E. coli cells and liposomes when increasing the peptide concentration above its effective antimicrobial concentration.…”
Section: Discussionsupporting
confidence: 91%
“…BF2 inhibited the growth of both Gram-negative and Gram-positive bacteria at remarkably low micromolar concentrations (Table 2). As reported previously for BF2 peptides purified from other species [9,10,11,12,13,14], our results highlight the BF2 elevated bactericidal activity. In regard to F2.3S and as predicted by in silico analysis, this peptide also presented a potent antibacterial activity against both E. coli and S. aureus reference cultures (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, a proline hinge may be more likely to induce translocation in peptides with less amphipathic character that do not readily form stable membrane-disrupting structures, such as DesHDAP1 and BF2, by increasing their ability to interact with lipids upon membrane entry. In fact, deformations around proline that increase membrane interactions have been observed in molecular dynamics simulations of BF2 interacting with lipid membranes [30]. The inclusion of a proline hinge may be less effective in inducing translocation in peptides that exhibit greater lytic potential, such as DesHDAP3, although additional examples of similar peptides with these properties would be helpful to support this assertion.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Table 1 notes how these sequences compare to the physiological sequences of hipposin, buforin I (BF1), buforin II (BF2) and parasin. Notably, the HipB region that was analogous to buforin II (BF2) included the F10W mutation that has been widely used in previous studies and shown to have analogous properties to the wildtype peptide [15, 16, 18, 20, 21]. …”
Section: 0 Materials and Methodsmentioning
confidence: 99%